2010
DOI: 10.1111/j.1524-4725.2009.01426.x
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Preoperative Biopsy-Site Photography for Identifying Cutaneous Lesions

Abstract: The patient incorrectly identified 45 of 271 surgical sites (16.6%), and the physician incorrectly identified 16 of 271 surgical sites (5.9%). The surgeon and the patient both incorrectly identified 12 of 271 sites (4.4%). All surgical sites were correctly identified with preoperative biopsy-site photography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 6 publications
0
37
0
1
Order By: Relevance
“…The following histologic features were evaluated from diagnostic biopsies: (1) the type and subtype of NMSC {SCC subtypes included in situ, well differentiated, moderately differentiated, keratoacanthoma [KA], acantholytic, or primary adenosquamous; BCC subtypes included nodular, superficial, pigmented, micronodular, morpheaform, or infiltrative}; (2) presence or absence of tumor at lateral and deep margins (Fig 1); and (3) closest distance of tumor to the lateral and deep biopsy margins and maximal dermal thickness measured in millimeters with an ocular micrometer (see Fig 1). Tangential biopsy specimens were bisected perpendicular to the long axis and submitted in toto.…”
Section: Methodsmentioning
confidence: 99%
“…The following histologic features were evaluated from diagnostic biopsies: (1) the type and subtype of NMSC {SCC subtypes included in situ, well differentiated, moderately differentiated, keratoacanthoma [KA], acantholytic, or primary adenosquamous; BCC subtypes included nodular, superficial, pigmented, micronodular, morpheaform, or infiltrative}; (2) presence or absence of tumor at lateral and deep margins (Fig 1); and (3) closest distance of tumor to the lateral and deep biopsy margins and maximal dermal thickness measured in millimeters with an ocular micrometer (see Fig 1). Tangential biopsy specimens were bisected perpendicular to the long axis and submitted in toto.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies confirm that both patients and physicians may commonly make site identification errors, and recommend photography to document biopsy sites. 11,12 Of note, a recent survey of US members of the American College of Mohs Surgery found that only 47% of physicians used photography to confirm biopsy sites. 13 …”
Section: Discussionmentioning
confidence: 97%
“…A prospective study of 333 patients found that 9 % of patients were unable to identify their surgical sites [19]. In another study of 271 surgical sites, patients incorrectly identified the 16.6 % surgical sites, and the physicians incorrectly identified 5.9 % of the surgical sites [20].…”
Section: Site Identificationmentioning
confidence: 98%